Latent Profile Analysis of Personality Dimensions Among Juvenile Offenders: relevance for Predicting Offending Seriousness - Wojciechowski, Thomas W. (Crime & delinquency, 2021)
There is a burgeoning base of research identifying personality as a predictor of offending. However, research has focused on personality dimensions, rather than full personality profiles as predictors. The present study utilized the Pathways to Desistance data to examine the relationship between personality profiles and offending. This sample comprised 1,354 juvenile offenders followed during the study period of 2000 to 2010. Latent profile analysis was used to identify patterns across dimensions to elucidate personality profiles. Negative binomial regression was used to examine profiles as predictors of offending. Results indicated that a two-profile model fit the data. Participants assigned to the Undercontrolled profile (high in neuroticism and low in all other dimensions) engaged in more serious offending than the Resilient profile.